1998
DOI: 10.1180/000985598545453
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nitrate to ammonium by sulphate green rust: activation energy and reaction mechanism

Abstract: Iron(II)-containing minerals are potential inorganic nitrate reductants in soils and sediments. Specifically, synthetic green rust (Fe4IIFeIII2(OH)12SO4.yH2O, GR) reduces nitrate to ammonium. The reaction of GR with two different nitrate salts, NaNO3 and Ba(NO3)2, has been compared. The reaction stoichiometry and the reaction order with respect to Fe(II) in GR does not change in the examined temperature range (15-50°C) irrespective of the nitrate salt used. Activation energies of 83.9±7.6 kJ mol-1 and 90.5±6.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 25 publications
(28 reference statements)
5
75
1
1
Order By: Relevance
“…In addition, these studies also demonstrated that the oxidized iron end product formed [amorphous Fe(III) (hydr)oxide or carbonate-containing green rusts] was dependent on the rate of Fe(II) oxidation by this organism (15,38). Both of these forms of iron are known to be unstable in the environment and are strong adsorbents for HMR (4,5,25,30,31).…”
Section: Resultsmentioning
confidence: 77%
“…In addition, these studies also demonstrated that the oxidized iron end product formed [amorphous Fe(III) (hydr)oxide or carbonate-containing green rusts] was dependent on the rate of Fe(II) oxidation by this organism (15,38). Both of these forms of iron are known to be unstable in the environment and are strong adsorbents for HMR (4,5,25,30,31).…”
Section: Resultsmentioning
confidence: 77%
“…Meanwhile, the methanol resulting from methane oxidation on green rust-like di-iron centres comprising the outer zone of the inorganic membrane will be further oxidized to formaldehyde at a Mo centre resembling that performing nitrite reduction [110,111]. The reducing power of the electrons issuing from this reaction is sufficient (cf.…”
Section: A Bioinspired Scenario For the Earliest Energy And Carbon Mementioning
confidence: 99%
“…On prolonged incubation (14 days), the green rusts gradually transformed into blackish brown-green. Previous studies have demonstrated that green rust will chemically react with nitrate to form magnetite and ammonia as the sole end products (18,19). Since green rust is one of the precursors of magnetite formed by D. suillum with nitrate as the electron acceptor, it is possible that the biogenic green rusts are abiotically reacting with the remaining nitrate to form magnetite.…”
mentioning
confidence: 99%